Branch Dieback of Syzygium paniculatum (Eugenia) - Aaron J. Palmateer; T. L. B. Tarnowski (EDIS)
Eugenia’s popularity stems from its dense, attractive foliage, the ease with which the canopy can be sculpted, and its relatively carefree management. But shortly after Hurricane Wilma in November 2005, a serious dieback disease began to affect nursery production of eugenia in the Homestead area. Since then, the disease has become prevalent, affecting local nurseries throughout South Florida. Learn more about this disease and its management in this 4-page fact sheet written by A. J. Palmateer and T. L. B. Tarnowski and published by the UF Department of Plant Pathology, July 2011.